Evaluasi minat peserta didik mts negeri 1 trenggalek terhadap cabang olahraga tenis lapangan - Nendra Febrianto; Sugeng Sulendro (JSH: Journal of Sport and Health, 2025)
This research aims to determine the interest of students at MTS Negeri 1 Trenggalek towards the sport of field tennis. Interest is a desire of an individual that arises because of feelings of liking and attachment to a thing or activity, without anyone ordering it, where it is continuously paid attention to without any coercion from other people, accompanied by a feeling of pleasure. To obtain maximum research results, researchers used techniques, namely interviews and questionnaires. This research was conducted with a sample of 40 respondents. Data was obtained by distributing a questionnaire to find out how interested students at MTS Negeri 1 Trenggalek were in the sport of field tennis.